Study on the Stability of Unpackaged CdS/CdTe Solar Cells with Different Structures - Guanggen Zeng; Xiaolan Liu; Yubo Zhao; Yuanmao Shi; Bing Li; Jingquan Zhang; Lianghuan Feng; Qionghua Wang (International Journal of Photoenergy)
In this work, the stability of unpackaged CdTe solar cells with different configurations was investigated according to the International Electrotechnical Commission IEC 61215-2016. The measurements of thermal cycling from -40°C to +85°C and 24-hour temperature cycling from -40°C to +85°C withstanding the effects of 20-hour penetration of 85°C were carried out in CdS/CdTe solar cells with structures of FTO/CdS/CdTe/Au, FTO/CdS/CdTe/back contact/Au, and FTO/MZO/CdS/CdTe/back contact/Au, respectively. The performances of these cells before and after the thermal aging experiments were investigated by using light and dark I‐V together with C‐V. The results reveal varied performance degradation before and after thermal aging in the cells with different structures. Among these, the most deteriorated device is the one without back contact (BC), whose efficiency decreased by 25.12% after thermal cycling accompanying an obvious roll-over phenomenon when forward bias was greater than open circuit voltage. On the contrary, the reduction in the efficiency was about 16.80% in the case cells with BC, and the roll-over phenomenon was not so significant. Furthermore, for the devices with optimized front contact of FTO/MZO, the thermal stability was improved obviously. Interestingly, short-circuit current density associated with the carrier concentration of cells remained relatively small variations compared with the change of Voc and fill factor. All the results indicated that an efficient back contact layer and an optimized front electrode were the indispensable structural elements to attain high stabilization in the CdS/CdTe solar cells.